Climate Change and Threatened Heritage: Archaeology's Burden - Gordon, Barry R (CUNY Academic Works, 2018)
Climate change and archaeology are currently intertwined, as more and more archaeologists around the world must deal with the effects it causes on the sites they work on. Threatened cultural resource sites are being swept away at alarming rates, and excavation projects are becoming more and more like salvage digs.